1993
DOI: 10.1111/j.1476-5381.1993.tb13816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endopeptidase‐24.11 inhibition and of atrial natriuretic peptide clearance receptor ligand on the response to rat brain natriuretic peptide in the conscious rat

Abstract: 1 The present studies examined the effect of (a) a specific endopeptidase-24.11 (E-24.11) inhibitor (candoxatrilat) and (b) a ligand for the atrial natriuretic peptide (ANP) clearance receptor (SC 46542) on the renal and blood pressure response to brain natriuretic peptide (BNP) in conscious rats.2 Infusion of BNP 200 ng kg-' min-' for 60 min produced a small rise in urinary sodium and guanosine 3':5'-cyclic monophosphate (cyclic GMP) excretion with a non-significant fall in mean arterial blood pressure. 3 Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…A small proportion of rats fail to compensate for the shunt and die in the first week post-surgery with sodium retention, manifest as pulmonary oedema and _ ascites (Winaver et al, 1988 . Consistent with our previous observations in these anb imals (Wilkins et al, 1992;Kirk & Wilkins, 1993) (Yamamoto et al, 1992;Ward et al, 1995). Third, Time (min) bradykinin is a substrate for both E-24.11 and ACE and coinhibition of these enzymes has been shown to potentiate sy-(a) Urinary sodium excretion (UNaV) in response to nergistically the natriuretic effects of bradykinin in anaes-[at, 3 mgkg-1 (0; n = l1) and sampatrilat, 0.1 mg kg-1 thetized dogs (Seymour et al, 1994).…”
Section: A -V Fistula Ratssupporting
confidence: 82%
See 1 more Smart Citation
“…A small proportion of rats fail to compensate for the shunt and die in the first week post-surgery with sodium retention, manifest as pulmonary oedema and _ ascites (Winaver et al, 1988 . Consistent with our previous observations in these anb imals (Wilkins et al, 1992;Kirk & Wilkins, 1993) (Yamamoto et al, 1992;Ward et al, 1995). Third, Time (min) bradykinin is a substrate for both E-24.11 and ACE and coinhibition of these enzymes has been shown to potentiate sy-(a) Urinary sodium excretion (UNaV) in response to nergistically the natriuretic effects of bradykinin in anaes-[at, 3 mgkg-1 (0; n = l1) and sampatrilat, 0.1 mg kg-1 thetized dogs (Seymour et al, 1994).…”
Section: A -V Fistula Ratssupporting
confidence: 82%
“…Endopeptidase (E-24.11) inhibitors reduce the metabolic clearance of atrial and brain natriuretic peptides (ANP and BNP) (Stephenson & Kenny, 1987;Danilewicz et al, 1989; Kenny et al, 1993) and enhance their renal and hypotensive actions in vivo (Trapani et al, 1989;Seymour et al, 1989;; Kirk & Wilkins, 1993). These properties suggest that E-24.11 inhibitors may be useful for the treatment of cardiac failure.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that URO is not completely resistant to NEP, may explain the stimulatory influence of SQ-28,603 on the renal effects of the peptide. But, we cannot exclude other possibilities, such as protection of other peptides with natriuretic activity, e.g., bradykinin (Ura et al, 1987) and BNP (Kirk & Wilkins, 1993;Mark Richards et al, 1993) and the inhibitory effects of the drug on sodium reabsorption in the proximal tubule (Cavero et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…NEP inhibition with (±) candoxatrilat reduced the clearance of ANP in both intact and nephrectomized rats (7), providing evidence for extrarenal sites of action. Further studies have shown that candoxatrilat (3 mg/kg) in rats alone had no significant effect on sodium excretion or blood pressure but markedly potentiated the natriuretic response to endogenous BNP (30). Pulmonary hypertension and right ventricular hypertrophy were induced by chronic hypoxia in rats.…”
Section: Pharmacodynamics Of Candoxatril Preclinical and Animal Studiesmentioning
confidence: 99%